2024
DOI: 10.1038/s41598-024-51752-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adjuvant systemic therapy following complete cytoreductive surgery in patients with recurrent granulosa cell tumours of the ovary

Harika Yumru Celiksoy,
Catriona Dickie,
Michael J. Seckl
et al.

Abstract: Aim of the present analysis is to compare the impact of antihormonal therapy versus cytotoxic chemotherapy versus a watch a wait approach on disease-free survival (DFS) in the adjuvant setting of patients who underwent complete cytoreductive surgery(CRS) for recurrent adult type granulosa cell tumours of the ovary (GCT). Moreover, we wished to identify prognostic risk factors for recurrence. We included recurrent GCT-patients who underwent CRS resulting in total macroscopic tumour clearance, treated in two gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…If one has received chemotherapy, the first option after surgery is follow-up, and the second is chemotherapy [ 30 ]. Yumru-Celiksoy et al found that no benefit was derived from adjuvant systemic treatment, of any type, following complete cytoreductive surgery in patients with GCT-relapse [ 31 ]. A study by Memorial Sloan Kettering showed that chemotherapy did not improve the recurrence-free interval of patients with GCTs, even though also non-tumor-free operated patients were included [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…If one has received chemotherapy, the first option after surgery is follow-up, and the second is chemotherapy [ 30 ]. Yumru-Celiksoy et al found that no benefit was derived from adjuvant systemic treatment, of any type, following complete cytoreductive surgery in patients with GCT-relapse [ 31 ]. A study by Memorial Sloan Kettering showed that chemotherapy did not improve the recurrence-free interval of patients with GCTs, even though also non-tumor-free operated patients were included [ 32 ].…”
Section: Discussionmentioning
confidence: 99%